Regionalism in Services : A Study of ASEAN - Gootiiz, Batshur; Mattoo, Aaditya (World Bank, Washington, DC, 2015)
Can regionalism do what multilateralism has so far failed to do—promote greater openness of services markets? Although previous research has pointed to the wider and deeper legal commitments under regional agreements as proof that it can, no previous study has assessed the impact of such agreements on applied policies. This paper focuses on the Association of Southeast Asian Nations (ASEAN), where regional integration of services markets has been linked to thriving regional supply chains. Drawing on surveys conducted in 2008 and 2012 of applied policies in the key services sectors of ASEAN countries, the paper assesses the impact of the ASEAN Framework Agreement on Services (AFAS) and the ambitious ASEAN Economic Community Blueprint, which envisaged integrated services markets by 2015. The analysis finds that over this period, ASEAN did not integrate faster internally than vis-à-vis the rest of the world: policies applied to trade with other ASEAN countries were virtually the same as those applied to trade with rest of the world. Moreover, the recent commitments scheduled under AFAS did not produce significant liberalization and, in a few instances, services trade policy actually became more restrictive. The two exceptions are in areas that are not on the multilateral negotiating agenda: steps have been taken toward creating regional open skies in air transport, and a few mutual recognition agreements have been negotiated in professional services. These findings suggest that regional negotiations add the most value when they are focused on areas that are not being addressed multilaterally.